Ethnographic Methods in Gypsy, Roma and Traveller Research Lessons from a Time of Crisis - Fotta, Martin; Gay y Blasco, Paloma (Bristol University Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This edited volume discusses the methodological and ethical challenges that researchers are currently facing whilst attempting to document the impact of the COVID-19 pandemic on Gypsy, Roma and Traveller communities throughout Europe.